The Inﬂuence and Challenges of Legal Politics in the Adoption of Foreign Law in the Era of Modernization - Nani Nuraeni; Tarmudi Tarmudi; Muhammad Muzhaﬀar Yahyayasir; Dear Dear; Sugianto Sugianto (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This research explores the transplantation of laws, especially how the process of adopting foreign laws into the Indonesian legal system faces challenges in the era of modernization, which often clashes with the norms that exist in society. Legal transplantation means the transfer of the legal system from one country to another with diﬀerent social contexts and legal systems, a phenomenon that is increasing as globalization progresses. Many countries adopt foreign laws to accelerate legal reform and meet international standards, but this process is not without its challenges. This often raises legal political problems, including the potential threat to national legal identity. The selection of foreign laws that are not careful can have a bad eﬀect on our current legal system. In this study, readers are invited to understand the importance of legal political challenges and the transplantation of foreign laws that are included in our national law.